DESKRIPSI PELAKSANAAN ADMINISTRASI KESISWAAN DI SEKOLAH MENENGAH ATAS NEGERI 4 PALOPO - Nursaeni, Nursaeni; Firmansyah, Firmansyah; Nurmiati, Nurmiati (Jurnal Manajemen Pendidikan, 2024)
The research uses a descriptive qualitative research approach. The data collection techniques used are observation and interviews. The subjects of this study are the vice principal of the student affairs section, operators, and students. The validity of the data was checked using extended participation data validation, observation persistence, and triangulation. The results of this study show that 1) The implementation of student administration at SMA Negeri 4 Palopo has been well structured starting from the admission of new students, the formation of committees to the welcoming of new students, the recording of students in the dapodik by the operator who is also responsible for the input of student data and school facilities, strict rules apply to all students including dressing, cleanliness, and the use of school facilities, being able to accept student transfers, arranging organizational activities to fully support activities carried out by the student council at school, to carrying out student graduation activities that have gone well. 2) Supporting factors in the implementation of student administration, namely the implementation of student administration, is supported by a strong commitment from all schools, namely teachers, staff to several students, starting from the admission of new students to the recording of alumni, as well as the availability of necessary facilities and infrastructure. The inhibiting factor is students who do not provide the requested data, thus hindering administrative staff.